Epidemiological Analysis Person, Time, and Place Dengue Fever Cases in Magelang City During 2019-2023 - Trisnawati, Erica Yunita; Indriani, Citra; Isworo, Adi; Wahyudi, Safaat (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to explore epidemiological characteristics of dengue fever cases in Magelang City during 2019-2023. Methods: Monthly dengue fever cases from 2019-2023 were extracted from the dengue passive surveillance database at the City Health Office. Data was analyzed descriptively based on time, person, and place. Results: There were 992 dengue cases with a mean incidence rate (IR) of 158 per 100,000 population, and the highest IR was observed in 2019 with 359 per 100.000. The annual case fatality rate was 0.5%, ranging from 0% to 1.3%. Males (52,2%) were observed higher than females (47.8%), and most cases were aged 12-25 years old (36.9%), with elderly (>= 60 years old) only counted for 14 (1.4%) cases. Dengue was reported throughout the year across the village within the city, with the peak of dengue season observed in January and February. Most notifications came from private hospitals (21%), and primary health care contributes about 0.5% of case notifications. Conclusion: The dengue case in Magelang City has characteristics similar to other areas in which the most affected were children and has a seasonal pattern, with the peak number of cases found in January to February and all areas within the city being endemic.